2020
DOI: 10.1029/2019ea001008
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the Water Environmental Capacity of a Seasonal River Using a Combined Watershed‐Water Quality Model

Abstract: The water environmental capacity (WEC) is an effective tool to solve the water pollution problem and achieve optimal water quality management. However, in a seasonal river, some important input data such as discharge and pollution concentration from river tributaries and lateral inflows are rarely available. This makes WEC calculating more challenging. In this study, the water environment system model that integrates hydrological process in the watershed and hydrodynamic water quality process in the river is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The runoff was simulated at a spatial resolution of 0.5° on a daily time step between 1971 and 2010, before being aggregated into monthly flows and averaged over 40 years. We compared the simulated runoff with measured values for six global basins, and the Nash–Sutcliffe efficiency (NSE) was greater than 0.7, indicating that the simulation results were good . We further took the ensemble mean runoff of the 15 models to eliminate the model error.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The runoff was simulated at a spatial resolution of 0.5° on a daily time step between 1971 and 2010, before being aggregated into monthly flows and averaged over 40 years. We compared the simulated runoff with measured values for six global basins, and the Nash–Sutcliffe efficiency (NSE) was greater than 0.7, indicating that the simulation results were good . We further took the ensemble mean runoff of the 15 models to eliminate the model error.…”
Section: Methodsmentioning
confidence: 99%
“…We compared the simulated runoff with measured values for six global basins, and the Nash−Sutcliffe efficiency (NSE) was greater than 0.7, 33 indicating that the simulation results were good. 36 We further took the ensemble mean runoff of the 15 models to eliminate the model error. Uncertainty analysis showed that using the ensemble mean runoff reduced uncertainty compared to using a single model (see SI Note 2 of the Supporting Information).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Scientific quantification of water environmental capacity is the basis of watershed pollutant management, and the accurate calculation of dynamic water environmental capacity is the key to achieving accurate management of river basins. At present, researchers have begun to explore management measures based on dynamic water environmental capacity [40,41]. This study calculated the dynamic water environment capacity based on the control unit.…”
Section: Analysis Of Dynamic Water Environment Capacitymentioning
confidence: 99%
“…Model groups used include steady hydrodynamic group including Qual2K and HEC-RAS and hydrodynamic model for unsteady flow including Mike 11 HD (Mike 11 2005), and then water quality simulation models such as Qual2K, Mike 11 AD, and ECO are used. Second, a hydraulic model for unsteady flow and a water quality model that takes into account tidal factors are used, based on which the RWEC is calculated for each reach (Ma et al 2020). The approach in this study presented includes six steps: Basin segmentation according to similar hydraulic principles and location of waste sources; Use of NAM to create hydraulic boundaries for unsteady flow models; Running the hydraulic model to determine the set of flow parameters Q i at the nodes (Supplementary Table S1).…”
Section: Introductionmentioning
confidence: 99%